The Warburg Institute : University of London School of Advanced Study - Warburg Institute (2005)
[Dt.:] Das Warburg-Institut der Universität London ist ein zentrales Forschungsinstitut der Bildwissenschaften und der Kulturgeschichte. Es ist der Erforschung der klassischen Antike und ihrer Auswirkungen auf die Kultur Europas in Literatur und Bildender Kunst gewidmet. Das Institut ging aus der Hamburger Bibliothek des Kunsthistorikers Aby Warburg (1866-1929) hervor, das 1921 zum Forschungsinstitut für Kulturgeschichte wurde. 1933 wurde das Institut von Deutschland nach London verlegt, 1944 wurde es in die Universität von London integriert. Die Web Site enthält eine nahezu unüberschaubare Anzahl an Unterteilungen und Linksammlungen, angegliedert sind die Bibliothek des Warburg-Instituts (über den OPAC der School of Advanced Study Library) sowie die Photosammlung und einige Online-Ausstellungen. - [Engl.:] The Warburg Institute of the University of London exists to further the study of the classical tradition, that is of those elements of European thought, literature, art and institutions which derive from the ancient world. It houses an archive, a library and a photographic collection. The institute stems from the personal library of the Hamburg scholar Aby Warburg (1866 1929). In 1921 this library became a research institute in cultural history. In 1933 it moved from Germany to London to escape the Nazi regime and in 1944 it was incorporated in the University of London. The homepage contains several extensive collections of links, the library of the Warburg Institute (via School of Advanced Study Library Catalogue), the photographical collection and some online exhibitions.